Analysis of Goods Tracking Website Quality on User Satisfaction Using the Webqual 4.0 Method: (Case Study Of The Cekresi.com Website) - Savarini, Rahma Auriel; Harlan, Fandy Bestario; Rahman, Fuad Arif; Fikri, Muhammad Jibran; Harianto, Alya Rossa (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The research aims to analyze the influence of both partially and simultaneously between usability quality, information quality and service interaction on user satisfaction with the Cekresi.com website. Data for this research was acquired from the results of the answers to questionnaires distributed to respondents. The analysis used Webqual 4.0, a widely accepted method for evaluating website quality and user satisfaction. Based on the study of the multiple linear regression analysis models used in this research, it is concluded that the quality of usability and the quality of service interaction are essential factors in improving the performance of the Cekresi.com website and have a positive and significant effect on user satisfaction Cekresi.com website. However, although information quality has a positive effect, it does not significantly impact the Cekresi.com website.